Transcranial alternating current stimulation combined with sound stimulation improves the cognitive function of patients with Alzheimer's disease: A case report and literature review - Liu, Yang; Tang, Can; Wei, Kailun; Liu, Di; Tang, Keke; Chen, Meilian; Xia, Xuewei; Mao, Zhiqi (Frontiers in Neurology, 2022)
Transcranial alternating current stimulation (tACS) is a relatively new non-invasive brain electrical stimulation method for the treatment of patients with Alzheimer's disease (AD), but it has poor offline effects. Therefore, we applied a new combined stimulation method to observe the offline effect on the cognitive function of patients with AD. Here, we describe the clinical results of a case in which tACS combined with sound stimulation was applied to treat moderate AD. The patient was a 73-year-old woman with a 2-year history of persistent cognitive deterioration despite the administration of Aricept and Sodium Oligomannate. Therefore, the patient received tACS combined with sound stimulation. Her cognitive scale scores improved after 15 sessions and continued to improve at 4 months of follow-up. Although the current report may provide a new alternative therapy for patients with AD, more clinical data are needed to support its efficacy. Trial registration Clinicaltrials.gov, NCT05251649.